Proton pump inhibitors interfere with the immunosuppressive potency of mycophenolate mofetil - Schaier, Matthias; Scholl, Markus; Scharpf, Dominik; Hug, Friederike; Bönisch-Schmidt, Sabine; Dikow, Ralf; Schmitt, Wilhelm; Schwenger, Vedat; Zeier, Martin; Sommerer, Claudia (Rheumatology, 2010)
Objectives. MMF is cleaved in the acidic milieu of the gastric compartment. However, its absorption might be impeded by proton pump inhibitors (PPIs), which suppress acid production and thus increase stomach pH. Since PPIs are widely used, it is useful to clarify whether the total drug amount of MMF is available in patients undergoing PPI treatment.Methods. We analysed 36 patients with autoimmune diseases under stable MMF maintenance therapy. Twenty-three patients received co-medication with pantoprazole; 13 patients received no treatment with PPIs or antacids. To assess the immunosuppressive potency, we measured mycophenolic acid levels and inosin monophosphate dehydrogenase (IMPDH) activity with a validated HPLC method in plasma samples collected pre-dose and at 0.5, 1, 1.5, 2, 3, 4, 5, 6, 8, 10 and 12 h after oral administration.Results. The mean MMF dosage of the non-PPI patients was 770 (249) mg/12 h and 771 (291) mg/12 h in pantoprazole-treated patients (NS). The total area under the curve of MMF showed a 37% reduction in PPI patients vs those treated with no PPIs (P < 0.01), and the maximum peak concentration of MMF was 60% lower in the pantoprazole patients (P < 0.001). The MMF exposure correlated with the inhibition of IMPDH activity. The area of enzyme activity curve was 42% higher in the PPI patients (P < 0.01).Conclusions. The co-medication of pantoprazole with MMF significantly influences the drug exposure and immunosuppressive potency of MMF in patients with autoimmune diseases. This finding might at least partly explain the different outcomes in studies using MMF for maintenance therapy.
Gesehen am10.08.2023